Answer:(
( x - 0)^2 + (y - 2)^2 = 40
Explanation:
We are asked to find the equation of a circle
Step 1: find the radius
( x - a) ^2 + ( y - b) ^2 = r^2
(a, b) - center of the circle
(x, y) - any point on the circle
r^2 - radius of the circle
Using the center
( a, b) = ( 0 , 2)
(x , y) = (6 , 0)
(a, b) = (0 , 2)
a = 0
b = 2
Inserting the values given into the equation
( x - a)^2 + ( y - b) ^2 = r^2
( x - 0)^2 + (y - 2)^2 = r^2
Step 2: sub (x, y) = ( 6 , 0)
x = 6
y = 0
( 6 - 0)^2 + ( 0 - 2)^2 = r^2
6^2 + (-2)^2 = r^2
36 + 4 = r^2
40 = r^2
Step 3: sub the radius into the equation
(x - 0)^2 + ( y -2)^2 = r^2
( x - 0)^2 + (y - 2)^2 = 40
The equation of the circle is
( x - 0)^2 + ( y - 2)^2 = 40